Pour une nouvelle identité dans la presse littéraire - Prodan Ioana-Crina (Anadiss, 2018)
Each society operates with linguistic and behavioral marks that influence (in) directly its socio-cultural development. Thus, it is necessary to specify that the written press represents a mirror of events, while revealing images and models of people and times that communicate through the meanings of cultural and social behaviors, transforming, through their immediate realization, the whole Romanian culture. The beginning of the last century is characterized by a remarkable evolution at the historical and cultural level. In fact, all segments of society have undergone a radical transformation in a broad process of modernization of the whole Romanian society, a key role being played by the intellectuals who visibly struggled to acquire a new status in the European world, to rally to the cultural trends of Europe.